Telaah Rumus Perhitungan Waktu Salat : Tinjauan Parameter dan Algoritma - Dini Rahmadani (University of Muhammadiyah Sumatera Utara, 2018)
Determination of prayer times using calculations and formulas. All times of prayer used in ordinary calculations generally use data when the position of the angle when the sun is in the zenith or when the sun is (entering) zuhur time. This value in the manual calculation is used for each calculation of prayer times at other times with the existing value argument not changing significantly, but in reality the sun position data (sun declination) will be different in value every time even though the data value only changes after 0, 1 point in a certain range, but this shows that the accuracy of declination data is needed on each count to get the value of prayer times which reaches the highest accuracy. Retrieving real time data on the position of the sun when entering criteria is also needed to obtain the truth in the basis of calculating high accuracy local prayer times. In addition, the use of time which is uni (same) must also be agreed upon so that the initial entry time can also be simultaneously. In the use of the application of the prayer time count and also in the book reference, it also has different values and criteria in the calculation, so that the user must also understand the parameters used in calculating prayer times so that he can use a calculation tool that is in accordance with the agreed criteria.